Long-Term Safety and Efficacy of Siluron2000 with Pars Plana Vitrectomy in the Treatment of Patients with Severe Vitreoretinopathy and Chronic Macular Holes - Arjmand P (Dove Medical Press, 2021)
Parnian Arjmand,1,2 Tina Felfeli,1,3,4 Efrem D Mandelcorn,1,2,4 Mark S Mandelcorn1,2,4 1Department of Ophthalmology and Vision Sciences, University of Toronto, Toronto, Ontario, Canada; 2Department of Ophthalmology, Toronto Western Hospital, University Health Network, Toronto, Ontario, Canada; 3The Institute of Health Policy, Management and Evaluation (IHPME), Dalla Lana School of Public Health, University of Toronto, Toronto, Ontario, Canada; 4Faculty of Medicine, University of Toronto, Toronto, Ontario, CanadaCorrespondence: Mark S Mandelcorn Tel +1 416 603 5885Fax +1 416 603 5834Email mark.mandelcorn@utoronto.caPurpose: Silicone oil intraocular retinal tamponade is a useful adjunct to pars plana vitrectomy (PPV) in the treatment of complex vitreoretinal conditions. Siluron2000, a modified silicone oil product containing an additional small, high molecular weight and low viscosity, very-long-chain silicone molecule, was developed to reduce post-operative silicone oil emulsification, a non-infrequent complication that occurs with low molecular weight silicone oil. This study was designed to assess the safety and efficacy of long-term Siluron2000.Patients and Methods: This was a single-center, retrospective, observational study. All consecutive patients undergoing PPV with intravitreal Siluron2000 injection between January 2017 and September 2019 with at least 6-month follow-up were identified based on billing codes.Results: A total of 57 eyes of 57 consecutive patients comprising 51 cases of proliferative vitreoretinopathy and 6 cases of recurrent full thickness macular hole were included. Median follow-up was 18 months. Emulsification occurred in 9 patients (15%). Retinal re-attachment was achieved in 47 patients (82%). The median time without silicone oil emulsification was 17 months. Of the cases with residual retinal detachment (RD) despite intravitreal Siluron2000, 4 (7%) were total RDs and 6 (10%) were inferior RDs with attached macula. The most common complications were glaucoma 12 (21%), cataract 11 (19%), and epiretinal membrane 2 (3.5%). There was no association between the duration of Siluron2000 and visual outcomes.Conclusion: Siluron2000 is an effective long-term tamponade agent in the treatment of complex vitreoretinopathy. Visual and anatomical outcomes are similar to those reported with higher mw silicone oil tamponade agents but with a lower emulsification rate.Keywords: emulsification, proliferative vitreoretinopathy, silicone oil, tamponade, vitreoretinal surgery, long-term oil